2010
DOI: 10.1007/s00192-010-1276-0
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the role of sacral nerve neuromodulation in lower urinary tract symptoms

Abstract: Sacral neuromodulation has been developed to treat chronic lower urinary tract symptoms, resistant to classical conservative therapy. The suspected mechanisms of action include afferent stimulation of the central nervous system and modulation of activity at the level of the brain. Typical neuromodulation is indicated both in overactivity and in underactivity of the lower urinary tract. In the majority of patients, a unilateral electrode in a sacral foramen and connected to a pulse generator is sufficient to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…In 1981, Tanagho and Schmidt subsequently demonstrated that stimulation of the S3 nerve root could be applied to a variety of GU pathologies (eg, incontinence and frequency) by modulating detrusor and sphincter action. 25,54 This research paved the way for the 1997 FDA approval of epidural sacral nerve root stimulation in the treatment of urinary urgency, frequency, urge incontinence, and retention. [54][55][56] The mechanism behind sacral nerve stimulation's (SNS) ability to modulate micturition is still being elucidated.…”
Section: Sacral Neuromodulationmentioning
confidence: 99%
See 4 more Smart Citations
“…In 1981, Tanagho and Schmidt subsequently demonstrated that stimulation of the S3 nerve root could be applied to a variety of GU pathologies (eg, incontinence and frequency) by modulating detrusor and sphincter action. 25,54 This research paved the way for the 1997 FDA approval of epidural sacral nerve root stimulation in the treatment of urinary urgency, frequency, urge incontinence, and retention. [54][55][56] The mechanism behind sacral nerve stimulation's (SNS) ability to modulate micturition is still being elucidated.…”
Section: Sacral Neuromodulationmentioning
confidence: 99%
“…described the first successful implantation of a SCS in the sacral spinal cord to initiate voiding in a patient with a spinal cord injury. In 1981, Tanagho and Schmidt subsequently demonstrated that stimulation of the S3 nerve root could be applied to a variety of GU pathologies (eg, incontinence and frequency) by modulating detrusor and sphincter action 25,54 . This research paved the way for the 1997 FDA approval of epidural sacral nerve root stimulation in the treatment of urinary urgency, frequency, urge incontinence, and retention 54–56 …”
Section: Treatment With Neuromodulationmentioning
confidence: 99%
See 3 more Smart Citations